Evaluation of body composition in body mass index matched PCOS and eumenorrheic non-PCOS college women - S., Rashmi; Hiremath, Netravati; P., Vanitha Reddy; B. M., Veena (International Journal Of Community Medicine And Public Health, 2025)
Background: Poly cystic ovarian syndrome (PCOS) is a genetic, hormonal and metabolic disorder that affects the women of reproductive age. PCOS is considered as one of the leading causes of infertility in women. Body composition evaluation is considered as one of the predictive factors in metabolic risk assessment. The present study was undertaken with an objective to assess the body composition distribution in body mass index (BMI) matched PCOS and non-PCOS women. Methods: A comparative case control study was conducted in BMI-matched, PCOS (n=55) and non-PCOS (n=55) college women aged between 18-25 years. PCOS subjects were selected based on the Rotterdam criteria. Prior to the study, ethical clearance certificate was obtained. Based on the BMI of PCOS cohort, non-PCOS healthy subjects (n=55) were selected with matched BMI. Body composition including anthropometry was analysed through bioelectrical impedance and standard protocols. Results: Non-PCOS and PCOS groups showed the non-significant differences in most of their anthropometric parameters except weight, neck size, and height. However, total per cent body fat and visceral fat levels were found to be significantly high in PCOS women with the p value of <0.001** and p=0.005 respectively. Additionally, skeletal muscle index, skeletal muscle mass, and total protein content were found to be significant low in PCOS at 99% CI. Conclusions: Visceral fat deposition and high percent body fat is generally associated with metabolic disturbance and hormonal changes and it was found to be highly prominent in the BMI matched PCOS women compared eumenorrheic healthy controls.